Facile preparation of polyacrylamide/chitosan/Fe3O4 composite hydrogels for effective removal of methylene blue from aqueous solution. (15th April 2020) - Zhang, Cheng; Dai, Yankai; Wu, Yinqiu; Lu, Guangwei; Cao, Zheng; Cheng, Junfeng; Wang, Kailun; Yang, Haicun; Xia, Yanping; Wen, Xiaoqian; Ma, Wenzhong; Liu, Chunlin; et al.
Highlights: Fe3 O4 nanoparticles were synthesized in situ in polyacrylamide/chitosan hydrogels. Magnetic hydrogels can adsorb methylene blue with a high adsorption capacity of 1603 mg/g. Kinetics and isotherm models of adsorption process can be better described. Adsorption mechanism is mainly based on electrostatic attraction. Abstract: In this study, Fe3 O4 magnetic nanoparticles were synthesized in situ in the polyacrylamide/chitosan (PAAm/CS) hydrogel networks. The obtained hydrogels are characterized by Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), X-ray diffraction (XRD), and Raman spectroscopy. The results confirm that the three-dimensional network structure of the hydrogels is incorporated with Fe3 O4 nanoparticles. The adsorption properties of PAAm/CS/Fe3 O4 hydrogels for methylene blue (MB) in aqueous solution were studied using Ultraviolet and visible spectrophotometry (UV–vis). The results show that when compared to PAAm/CS hydrogels, PAAm/CS/Fe3 O4 hydrogels can adsorb MB with higher adsorption capacities of approximately 1603 mg/g, and the kinetics and isotherm models of the adsorption process could be better described by the pseudo-first order model and Langmuir isotherm model, respectively. Due to the facile preparation, high adsorption capacity, and low cost, the PAAm/CS/Fe3 O4 hydrogels are good adsorbents for MB and exhibit significant potential in the treatment of sewage.